Analysis of a 40-Story Office Building Combining a Post Tensioned Flat Slab with Separated Gravity Lateral Resisting Implementation - Alexandra Patricia Andriani; Jessica Sjah; Indra Nurudin Fathoni; Nuraziz Handika (Engineering Proceedings)
Compared to other countries, the adoption of post-tensioned flat slab (PTFS) in Indonesia is relatively limited due to the susceptibility of flat slab to lateral forces. Nevertheless, flat slabs in high seismic zones scan still be achieved by utilizing the separated gravity lateral resisting (SGLR) system. This study analyzes a 40-story office building by comparing the structural response, volume, and cost of PTFS with conventional structures. The findings reveal that PTFSs exhibit greater story drift and displacement but experience reduced story shear and overturning moments with a reduction in concrete volume of up to 10% and a 6% decrease in overall costs.